Typology Of Spas Interior In 5-Star City Hotels In Peninsular Malaysia - Wee, Seiw Wai (2012)
The original meaning of spa, sanus per aquam (SPA) is Latin for “health through or by water”. Spa provides various traditional treatment practices hereditary including steam bath, massages and all the treatments using essence of flowers and plants for healing purpose. The spa industry is experiencing very fast growth in Malaysia but there are still many people that may not really understand the spa types and definitions. This research examined the typology of interior design of spas in 5-star city hotels in Peninsular Malaysia. The problem statements attempted to identify the existing designs in the spa do not meet the design criteria and elements that should exist in the spa.